Zero-shot Cross-lingual Transfer of Neural Machine Translation with Multilingual Pretrained Encoders - Chen, Guanhua; Ma, Shuming; Chen, Yun; Dong, Li; Zhang, Dongdong; Pan, Jia; Wang, Wenping; Wei, Furu (EMNLP 2021, 2021)
Previous works mainly focus on improving cross-lingual transfer for NLU tasks with multilingual pretrained encoder (MPE), or improving the translation performance on NMT task with BERT. However, how to improve the cross-lingual transfer of NMT model with multilingual pretrained encoder is under-explored. In this paper, we focus on a zero-shot cross-lingual transfer task in NMT. In this task, the NMT model is trained with one parallel dataset and an off-the-shelf MPE, then is directly tested on zero-shot language pairs. We propose SixT, a simple yet effective model for this task. The SixT model leverages the MPE with a two-stage training schedule and gets further improvement with a position disentangled encoder and a capacity-enhanced decoder. The extensive experiments prove that SixT significantly improves the translation quality of the unseen languages. With much less computation cost and training data, our model achieves better performance on many-to-English testsets than CRISS and m2m-100, two strong multilingual NMT baselines.